The A to E of airway disease. - Pavord, I; Wardlaw, A (2010)
The terms asthma and chronic obstructive pulmonary disease have evolved from their original very specific physiology-based definition to describe additional disease entities such as symptoms, airway inflammation and airway structure. We argue that as a result there is widespread confusion about what the terms mean. This has become a significant hurdle to optimal disease management and drug development. We propose that these disease labels should be replaced with a new alphabetical assessment tool for characterizing airway disease, which provides a checklist of five relatively independent factors potentially responsible for morbidity in patients with airway disease: Airway hyperresponsiveness, Bronchitis, Cough reflex hypersensitivity, Damage to the airway and surrounding lung and Extrapulmonary factors. We speculate that the use of this system to characterize airway disease will improve outcomes by promoting better targeting of new and existing treatments.